A fast and sensitive ultra-high-performance liquid chromatography-tandem mass spectrometry method for determining mefentrifluconazole in plant- and animal-derived foods. Issue 9 (2nd September 2019) - Zhang, Ying; Wu, Xiaohu; Li, Xianbin; Duan, Tingting; Xu, Jun; Dong, Fengshou; Liu, Xingang; Guo, Luyao; Zheng, Yongquan
ABSTRACT: A rapid and sensitive ultra-high-performance liquid chromatography-tandem mass spectrometry method, in conjunction with multiwalled carbon nanotube purification, was developed to determine the mefentrifluconazole levels in grapes, cucumbers, tomatoes, peppers, wheat, maize, eggs, milk, pork, chicken, and fish. After purification, tandem mass spectrometry of mefentrifluconazole required <3.0 min. Matrix-matched external standard curves were used to quantify the residual mefentrifluconazole. The method meets the requirements of the European Union Document SANTE/11813/2017. Quantification was linear between 5 and 500 μg/kg (R 2 ≥ 0.9988), and both the intra- and interday relative standard deviations were ≤13.7%. Analyte recovery ranged from 81.5% to 107.6%. The limit of mefentrifluconazole quantification was 5 μg/kg for all matrices. The method successfully detected and quantified mefentrifluconazole that had been applied to cucumbers and tomatoes grown in a test field. These results imply that the proposed method is effective and reliable for detecting mefentrifluconazole residues in plant- and animal-derived foods.